CULTURAL CONNOTATIONS IN JHUMPA LAHIRI’S THE NAMESAKE - Kaur, Paramjit (International Journal of Research -GRANTHAALAYAH, 2017)
Jhumpa Lahiri’s novel The Namesake intricately explores themes of identity, cultural dislocation, and assimilation in a diasporic context. This paper critically analyzes the cultural connotations embedded within the novel, focusing on the immigrant experience, generational conflicts, and the significance of names and identity. Through a close reading of the text and secondary sources, this research seeks to unravel how Lahiri portrays cultural hybridity and the challenges of maintaining one’s heritage while adapting to a new society. The novel highlights the struggles of first- and second-generation immigrants as they navigate the complexities of belonging to two different cultures. Lahiri emphasizes the importance of names as symbols of cultural heritage and self-identity, showcasing the tensions between tradition and modernity. This study contributes to the discourse on immigrant literature by exploring how The Namesake reflects the broader experiences of diaspora communities.